Estudantes bolsistas do ensino médio/técnico na rede privada: equidade de oportunidades ou falta de amparo? - Müller, Franciele (Universidade do Vale do Rio dos Sinos, 2024)
This research aimed to look at the reality of high school and technical scholarship students in a private institution, in the city of Gravataí (metropolitan area of Porto Alegre/RS), seeking to investigate whether there is equity in opportunities or a lack of support. The paper has a qualitative nature, triggered by a case study. First, the construction of education in Brazil was contextualized - both in the public and private spheres -, understanding public policies for providing access and looking at adolescence as a phase of change, full of meanings and plausible acceptance. In a connection between Social Sciences and Education, Sen, Rawls, and Freire led the reflections, highlighting freedoms, fairer societies, and critical education. The analysis in the school context took place through interviews, questionnaires, and focus groups, adapting the methods to the needs of the people in the environment. Managers, teachers, families, and students participated in the research, in order to provide a multifocal view of the reality experienced by the scholarship holders, from previous experiences to everyday ones. It is concluded that the school seeks to promote equal opportunities, however, extra activities contexts consist of meeting this reality, making it difficult for young people to integrate due to great external differences. Aspects of everyday life, such as the “feeling of belonging”, happen in detail, through the offering of some material goods – such as uniforms, in the context of technical education -, but, mainly, intangible goods – as an adaptation of “ala minuta” day, assured access (working bus card), enhancing capabilities and helping to strengthen self-esteem. Therefore, it is possible to observe that the school cares about the students who permeate this environment, and, sometimes, two basic - and forgotten - aspects can change the entire context: listening and welcoming them, therefore, it is through active listening that the sense of belonging is consolidated.
Keywords: Estudantes; Bolsas de estudos; Ensino privado; Students; Scholarship; Private education; ACCNPQ::Ciências Humanas::Sociologia